System for Effective Remote Control and Monitoring of Radiation Situation Based on Unmanned Aerial Vehicle - Zabulonov, Yu.L.; Burtnyak, V.M.; Odukalets, L.A. (Science and Innovation, 2024)
The necessity to create a new technology based on the use of unmanned aerial vehicle (UAV) for controlling the radiation situation in the areas exposed to radiation sources has been justified. The basic specifications of octocopter and developed spectrometric complex have been given. The use of proposed facilities has been showed to enable detection of both spot and distributed sources of radioactive contamination under real conditions.